Pendampingan Penyusunan Laporan Keuangan Pada Vigaza Farm Sleman Yogyakarta - Saputri, Evieana Riesty; Niandari, Nanik; Rahimah, Rahimah; Erdi, Tio Waskito; Herbowo, Herbowo (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The community service program aims to provide assistance in preparing simple financial reports for MSMEs so that they can carry out good bookkeeping. The target of this community service program is Vigaza Farm Sleman Yogyakarta which is engaged in quail farming located at Palgadin, 03/18 Sinduharjo Ngaglik Sleman Yogyakarta, 55581. The program is carried out face-to-face from March 3 to April 31, 2025. The methods used in this community service are counseling and assistance. The results of this program are that partners understand bookkeeping problems and the preparation of standard financial reports using the Ms. Excel program. Therefore, there is an improvement in the preparation of financial reports produced by Vigaza Farm Sleman Yogyakarta